Insights from China: understanding the impact of community resilience and government trust in psychological resilience and anxiety during COVID-19 - Hu, Yue; Huang, Yuxin; Zhang, Hua; Fang, Min; Chen, Guobang (Frontiers in Public Health, 2023)
Background: COVID-19 has the potential to greatly impact an individual mental well-being. However, an individual's psychological resilience, combined with support from their community and government disaster relief efforts can aid individuals in confronting crises with a positive mindset. The purpose of this study is to investigate how individuals, across three dimensions of individual resilience perception, community resilience perception, and government trust perception, mitigate individual anxiety during COVID-19.Methods: This study employed an online survey method that was not restricted by geographical location. Data collection took place from January 2022 to June 2022, and the valid questionnaires covered all 31 provinces, autonomous regions, and municipalities in China. The assessment of community resilience was conducted employing the Conjoint Community Resilience Assessment Measure-10 (CCRAM-10). Structural Equation Modeling (SEM) was also used to examine the relationship between community resilience, government trust, individual psychological resilience, and anxiety.The SEM results reveal that individual psychological resilience is significantly negatively correlated with anxiety (b = -0.099, p < 0.001), while there is a significant positive correlation between community resilience perception (b = 0.403, p < 0.001) and government trust (b = 0.364, p < 0.001) with individual psychological resilience. Furthermore, government trust perception enhances psychological resilience, consequently reducing anxiety (b = -0.036, p < 0.001). The results also revealed that women and increasing age had a mitigating effect on individual anxiety during COVID-19.Conclusions: Individual's mental state is influenced on multiple dimensions during COVID-19. Not only can individual psychological resilience better cope with anxiety, but support at the community and government dimensions has a significant impact on individual psychology. These resources can enhance the resilience of both individuals and communities, helping them better cope with stress and difficulties.